To Appraise the Learning protocol of Linguistic English Writing as a Proper Skill of English for Medical Purposes (Pascasarjana Universitas HKBP Nommensen, 2024)
The aims of this linguistic study was to appraise: the participant' feelings on teacher approach to educating in academic writing process, the weak and strong points of the model applied during the teaching academic writing in EMP and, and the participants' linguistic ideas and impressions at applying new ways, for material delivery of EMP.Data were released based on chosen variables: their occupation, year of education, and knowledge with writing techniques discovered that there were no important statistical differences at (a = 0.05) in the use of educational techniques. There are statistically important differences in using educational techniques units because of the year of teaching adaptable, in favors of, the third and fourth year academics. The findings also, disclosed that there are statistically significant differences in using technique units due to the practice with other variable, in favors of academics with no techniques use practice. The linguistic techniques can thus assist higher education programmers to identify, track, monitor, and treat at the university to educate, for teaching and learning medicine to strive in educating specialized writing. Given the linguistic benefits, it seems indispensable to apply the advantages of the survey, because studying hard to develop the technique, and implementing them in academic writing education is a theory.